Increased immune activation by pathologic α-synuclein in Parkinson's Disease - Grozdanov, Veselin D.; Bousset, Luc; Protzek, Meike; Bliederhäuser, Corinna; Meier, Christoph; Madiona, Karine; Pieri, Laura; Kiechle, Martin; McLean, Pamela J.; Kassubek, Jan Rainer; Behrends, Christian; Ludolph, Albert C.; et al. (Annals of neurology, 2019)
Objective Excessive inflammation in the central nervous system (CNS) and the periphery can result in neurodegeneration and parkinsonism. Recent evidence suggests that immune responses in Parkinson disease patients are dysregulated, leading to an increased inflammatory reaction to unspecific triggers. Although α-synuclein pathology is the hallmark of Parkinson disease, it has not been investigated whether pathologic α-synuclein is a specific trigger for excessive inflammatory responses in Parkinson disease. Methods We investigated the immune response of primary human monocytes and a microglial cell line to pathologic forms of α-synuclein by assessing cytokine release upon exposure. Results We show that pathologic α-synuclein (mutations, aggregation) results in a robust inflammatory activation of human monocytes and microglial BV2 cells. The activation is conformation- dependent, with increasing fibrillation and early onset mutations having the strongest effect on immune activation. We also found that activation of immune cells by extracellular α-synuclein is potentiated by extracellular vesicles, possibly by facilitating the uptake of α-synuclein. Blood extracellular vesicles from Parkinson disease patients induce a stronger activation of monocytes than blood extracellular vesicles from healthy controls. Most importantly, monocytes from Parkinson disease patients are dysregulated and hyperactive in response to stimulation with pathologic α-synuclein. Furthermore, we demonstrate that α-synuclein pathology in the CNS is sufficient to induce the monocyte dysregulation in the periphery of a mouse model. Interpretation Taken together, our data suggest that α-synuclein pathology and dysregulation of monocytes in Parkinson disease can act together to induce excessive inflammatory responses to α-synuclein. ANN NEUROL 2019;86:593-606
Gesehen am 16.06.2021